2145 Hard Red Wheat - Fritz, Allan; Martin, T. Joe; Shroyer, James P. (My University, 2002)
An informational publication about 2145 Hard Red Wheat, a new hard red winter wheat variety developed cooperatively by K-State Researchand Extension and the Agricultural Research Service (USDA-ARS).
L923_2002-05
Keywords: L923; Crops; L